2019
DOI: 10.3892/ijmm.2019.4172
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of proliferation and differentiation of gingiva‑derived mesenchymal stem cells by concentrated growth factors: Potential implications in tissue engineering for dental regeneration and repair

Abstract: The aim of the present study was to evaluate the proliferation and osteogenic differentiation ability of gingiva-derived mesenchymal stem cells (GMSCs) cultured with different concentrations of concentrated growth factors (CGF). GMSCs were isolated from gingival connective tissues and characterized by flow cytometry, immunofluorescence staining and immunohistochemical staining. Cell proliferation activity was determined by the MTT assay, and the effect of CGF on MCSCs was detected with the Cell Counting Kit (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 37 publications
4
26
0
2
Order By: Relevance
“…Our results further revealed that with the concentrations of CGF from 5-10%, signi cant promotion effects on the proliferation and migration of BMSCs in a dose-dependent manner were shown. However, higher concentrations of CGF extract do not guarantee stronger promoting effects, even will have inhibitory effects on the cultured cells [19,35,36]. In this article, the effect of a 20% CGF extract was inferior to those of the 10% group, which is consistent with other's results [19,37,38].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our results further revealed that with the concentrations of CGF from 5-10%, signi cant promotion effects on the proliferation and migration of BMSCs in a dose-dependent manner were shown. However, higher concentrations of CGF extract do not guarantee stronger promoting effects, even will have inhibitory effects on the cultured cells [19,35,36]. In this article, the effect of a 20% CGF extract was inferior to those of the 10% group, which is consistent with other's results [19,37,38].…”
Section: Discussionsupporting
confidence: 89%
“…First, CGF extracts contains not only growth factors that favor osteogenic but also unosteogenic cytokines [39]. At high concentrations, the inhibitory effects of the in ammatory cytokines in CGF might play a dominant role [19]. Second, it has previously been proposed that pH value is affected by the change in platelet count, which may negatively affect cell proliferation [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Gingiva-derived MSCs (GMSCs), a novel type of multipotent MSCs showing potential self-renewing multipotent differentiation into several cell lineages and immunomodulatory capacities, has been described [34,35]. GMSCs attract an increasing consideration for their easy isolation, stable phenotype, normal karyotype, high proliferative capacity and telomerase activity after long-term culture [36]. GMSCs and PDLSCs are considered to be optimal candidates for tissue engineering and cell-based therapies [37].…”
Section: Morphological Features and Phenotypic Characterization Ofmentioning
confidence: 99%